(untitled) (International Current Pharmaceutical Journal, 2012)
Some tablet pharmaceutical preparations containing Gliclazide as sole active ingredient, are marked now in Indone-sia. The determination of the component of preparation both qualitatively and quantitatively is important to ensure quality of the product. This research is aimed to develop a TLC method to analyze gliclazide in its single component tablet formulation. Gliclazide were dissolved with chloroform. Gliclazide was chromatographed on silica Gel 60 F254 TLC plate using toluene: ethyl acetate in the ratio of 1:1 (v/v) as mobile phase. Gliclazide showed Rf value of 0.58 and was scanned at 234nm using Camag TLC Scanner 3. This method validation showed a good linearity with correlation coefficient (r) of 0.999 while the coefficient of variation of the regression function (Vx0) = 2.406%. Specificity showed calculation of purity and identity more than 0.99. The limit of detection (LOD) and the limit of quantification (LOQ) of the method was respectively 28.78 and 86.35 ng/spot respectively. The mean absolute recovery of Gliclazide from the simulation sample was 100.5% ± 0.113 and the method precision was less than 5.3% whereas the mean of the recovery data was 100.3%. The proposed method has been applied to the determination of Gliclazide in commercial tablet formulations and the recovery of label claim were100.494%±0.348 for brand A and 100.111%±1.257% for brand B. The developed method was successfully used for the assay of gliclazide. The method is simple, sensitive and precise; it can be used for the routine quality control testing of marketed formulations. DOI: http://dx.doi.org/10.3329/icpj.v1i10.11852 International Current Pharmaceutical Journal 2012, 1(10): 332-335